2003
DOI: 10.1007/s00244-002-0116-8
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Daphnids Ceriodaphnia dubia and Daphnia ambigua for Their Utilization in Routine Toxicity Testing in the Southeastern United States

Abstract: U.S. regulatory agencies commonly require effluent toxicity testing with Ceriodaphnia dubia--a practice that has led to the criticism that this species and test protocol often does not reflect local taxa or site-specific conditions. Using an indigenous test species may produce a more realistic model of local effects and may minimize test endpoint variance due to regional differences in water quality. This study addressed the substitution of C. dubia with Daphnia ambigua for toxicity testing in the southeastern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
39
2
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 0 publications
7
39
2
1
Order By: Relevance
“…Chloride IC50 values for C. dubia were similar to those determined elsewhere in low-hardness water [10] and in moderate-hardness water [9,11]. The IC50 value for SO 4 2À determined in moderate-hardness water was close to that determined by Soucek [27], who also tested Na 2 SO 4 in a similar water formulation.…”
Section: Discussionsupporting
confidence: 69%
“…Chloride IC50 values for C. dubia were similar to those determined elsewhere in low-hardness water [10] and in moderate-hardness water [9,11]. The IC50 value for SO 4 2À determined in moderate-hardness water was close to that determined by Soucek [27], who also tested Na 2 SO 4 in a similar water formulation.…”
Section: Discussionsupporting
confidence: 69%
“…We found cladocerans and copepods to be the most sensitive taxa to salts, with copepods being slightly more tolerant than cladocerans. Both taxa were rare or absent in pools with mean concentrations [1,200 mg L -1 , and were more sensitive to concentrations of salts in outdoor mesocosms relative to laboratory tests with NaCl (e.g., Harmon et al 2003;Sarma et al 2006). Based on field surveys, Hart et al (1991) reported that cladocerans are rarely found in natural habitats in Australia with salinities [1,000 mg L -1 , which is consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…In soft water (under 20 mg/L CaCO 3 ) the survival and reproduction of snails were poor. With the microcrustacean Ceriodaphnia dubia, Harmon et al (2003) observed a significant reduction in reproduction when the organisms cultured in moderately hard water were exposed to low hardness waters from streams in South Carolina, USA. The effects of hardness and alkalinity on the reproduction of C. dubia in cultivation water and in tests with water samples were evaluated by Lasier et al (2006).…”
Section: Discussionmentioning
confidence: 99%